"Do-Live-Well": A Canadian framework for promoting occupation, health, and well-being: « Vivez-Bien-Votre Vie » : un cadre de référence canadien pour promouvoir l'occupation, la santé et le bien-être. (February 2015) - Moll, Sandra E.; Gewurtz, Rebecca E.; Krupa, Terry M.; Law, Mary C.; Larivière, Nadine; Levasseur, Mélanie
Background: Occupational therapists can bring a unique and valuable perspective to the national dialogue on health promotion. Current approaches have a narrow focus on diet and exercise; a broader focus on occupation has the potential to enrich understanding regarding forces that contribute to health and well-being. Purpose: A new "Do-Live-Well" framework will be presented that is grounded in evidence regarding the links between what people do every day and their health and well-being. Key Issues: Elements of the framework include eight different dimensions of experience and five key activity patterns that impact health and well-being outcomes. Personal and social forces that shape activity engagement also affect the links to health and well-being. Implications: The framework is designed to facilitate individual reflection, community advocacy, and system-level dialogue about the impact of day-to-day occupations on the health and well-being of Canadians.